學校評鑑制度：香港經驗的反思School Evaluation Policy: A Reflection from Hong Kong Experience - 楊思賢 Sze-Yin Shirley Yeung (Higher Education Foundation, 2013)
近年來，「證據為本」的學校自我評鑑（自評）成為世界潮流。學校自評機制意謂學校可自行評鑑其教育質素，據之不斷自我改進，以期自我完善。香港教育當局近年也把過往由官方主導的視學方式改變為學校自評與外評機制，同時把學校教育目標轉化成為質素「表現指標」，用意是為學校提供一個公平基礎進行自評和與他校比較，激發學校持續進取和履行「問責」精神。研究者藉由參與觀察的研究方式，探究一次學校外評經驗，並透過觀察結果，分析此類學校評鑑措施與課程改革實施的關係，反思該政策能否促成優質教育目標的達成，最後提出建議。Evidence-based school self-evaluation has been a recent trend in school improvement movement. School self-evaluation (SSE) is a mechanism through which schools evaluate themselves with regard to the quality of education, improve themselves continuously and develop themselves into quality schools. The Education Bureau in Hong Kong has followed this trend and launched a school evaluation policy -- School Self Evaluation (SSE) and External School Review (ESR). The pair of evaluation measures was initiated to help schools to evaluate their own effectiveness, to ensure public accountability and to achieve self development. To support SSE and ESR, a framework of Performance Indicators (PI) was provided to help stakeholders to assess school performance. This paper reports a study of a ESR experience. By participant observation method, the study inquires into the underlying agenda of the policy. The paper wishes to critically analyze this current educational policy and inquire into the relation between SSE/ESR and the official intent to enforce and control curriculum change and discusses the impact of the policy on curriculum change and quality education.